Relationships between high-density lipoprotein cholesterol and depressive symptoms: Findings of the Korean National Health and Nutrition Examination Survey (KNHANES). (30th July 2016) - Shin, Hee-Young; Kang, Gaeun; Kang, Hee-Ju; Kim, Sung-Wan; Shin, Il-Seon; Yoon, Jin-Sang; Kim, Jae-Min
Abstract: Although serum cholesterol has been associated with late-life depression, few studies on the associations between lipids and depression among middle-aged adults have been performed. This study examined associations between serum lipid levels and depressive symptoms in Korean middle-aged adults. We used data from 8207 participants aged 40–64 years who completed a questionnaire about their experience of depressive symptoms over the last year as part of the 2010–2012 Korean National Health and Nutrition Examination Survey. Higher HDL-C levels were significantly associated with an elevated risk of depressive symptoms (OR=1.32; 95% CI=1.09–1.60) after adjusting for other covariates. Highlights: Higher HDL-C levels were associated with depressive symptoms in middle-aged adults. The role of lipid levels on depression may be different between middle and old ages. Vascular depression hypothesis could be pursued in adult populations.